Dihydroxyphenylglycol as a Biomarker of Norepinephrine Transporter Inhibition by Atomoxetine: Human Model to Assess Central and Peripheral Effects of Dosing. Issue 6 (December 2016) - Bieck, Peter R.; Leibowitz, Mark; Lachno, D. Richard; Ledent, Edouard; Padich, Robert; Jhee, Stan
Abstract : Abstract: To assess the primary metabolite of norepinephrine, 3, 4-dihydroxyphenylglycol (DHPG), as a sensitive biomarker for norepinephrine transporter (NET) function and the relationship of DHPG measured peripherally and centrally, NET was antagonized with 80 mg/d atomoxetine for 18 days. Twelve healthy subjects were treated with atomoxetine in an open-label, multiple-dose exploratory study. Plasma atomoxetine reached steady state by day 6, and the pharmacokinetic results demonstrated availability of atomoxetine to the central nervous system. The cerebrospinal fluid (CSF)/plasma ratios of atomoxetine based on area under concentration-time curve from 0 to 12 hours postdose (AUC0–12), maximum concentration (Cmax ), and predose were 0.3%, 0.2%, and 11%, respectively. Plasma from atomoxetine-treated subjects (ex vivo) significantly inhibited radioligand binding to human NET ( P < 0.001) only 1 hour after dosing. Plasma DHPG and DHPG/norepinephrine (ratio) during repeated posture tests were reduced significantly ( P < 0.001) on day 5 and stayed significantly reduced up to 1 day after treatment. In CSF, both DHPG and the ratio were significantly reduced ( P < 0.001) on day 18. Urine results showed significant decreases for both DHPG and the ratio ( P = 0.010 to P < 0.001). Brain-derived neurotrophic factor in CSF was lesser than the limits of detection. The findings suggest that NET blockade can be assessed with DHPG concentration or with the ratio in plasma, CSF, and urine. The data suggest that DHPG is a useful biomarker to proactively assess the pharmacological activity of compounds intended to inhibit NET activity within the brain. The study shows that CSF is a medium for early identification and quantification of biomarkers useful in assessing novel neuroscience targets. Abstract : Supplemental digital content is available in the text.